Cold Intimate Partner Violence: Lived Experiences of South African Victims - Letsoalo, Daniel Lesiba; Seeletse, Selegile Philda (Psychocentrum Review, 2025)
This qualitative study, grounded in social constructivism paradigm and a single case study design, investigated the lived experiences of victims of cold violence in intimate relationships. The study was conducted at the rural Bapong crisis centre in Bapong Village, North-West Province, South Africa. Data were generated through individual face-to-face semi-structured interviews and inductively analysed through reflexive thematic analysis (RTA). The analysis revealed various main themes and subthemes which included inter alia prevalence of cold violence in intimate relationships, insults, confusion and manipulation as a means to maintain cold intimate partner violence (IPV), managing victims access to possessions as a means to maintain cold IPV, emotional and psychological effects and measures and support systems that can effectively aid and enhance the well-being of victims of cold IPV. The findings revealed that cold violence is a common occurrence in intimate relationships. Additionally, the research revealed detrimental emotional and psychological effects stemming from cold violence within intimate partnerships. The results underscore the need for tailored support and intervention approaches for victims of cold IPV. To achieve a more nuanced understanding, more studies are needed within this research niche to refine and guide the development of targeted, context-specific interventions, strategies, and/or guidelines, especially in countries with high levels of IPV such as South Africa.